2013
DOI: 10.1021/ac402328w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ion Transfer in Supported Liquid Membrane Systems: Electrochemical Control over Membrane Distribution

Abstract: A polarization study carried out on a thin supported liquid membrane separating two aqueous compartments is presented. Transfer of both the ionized and uncharged form of an organic tracer dye, rhodamine B ([9-(2-carboxyphenyl)-6-diethylamino-3-xanthenylidene]-diethylammonium chloride), across supported liquid membranes composed of one of 1-octanol (octan-1-ol), 1,9-decadiene (deca-1,9-diene), 1,2-dichlorobenzene, or nitrophenyl octyl ether (1-(2-nitrophenoxy)octane) was studied using cyclic voltammetry and UV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 72 publications
4
31
0
Order By: Relevance
“…1, with increasing applied potential, the oxidation of Ag results in the cation transfer from the sample to the inner solution of the electrode. Increasing the hydrophilicity of the ions results in an increasing potential to transfer ions across the membrane [31]. Therefore, the cation exchanger membrane with its higher selectivity in the Hofmeister series exhibits a high preference for TBA + over other ions in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…1, with increasing applied potential, the oxidation of Ag results in the cation transfer from the sample to the inner solution of the electrode. Increasing the hydrophilicity of the ions results in an increasing potential to transfer ions across the membrane [31]. Therefore, the cation exchanger membrane with its higher selectivity in the Hofmeister series exhibits a high preference for TBA + over other ions in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…According to the law of mass conservation, the relation between the initial concentrations in W and O and the concentrations in W and O after the distribution equilibrium can be expressed as eqn. (22).…”
Section: Theorymentioning
confidence: 96%
“…As for the ion transport between two aqueous phases across a liquid membrane, the author's group and Horvá th [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 and Horvai reported the analytical method by considering the ion transfers at two W j O interfaces [13][14][15]. Several research groups have studied the permeation properties based on the analysis of the interfacial transfer and the membrane transport [16][17][18][19][20][21][22]. Nakamura and Osakai explained the plateau region observed for hydrophobic drugs based on the theoretical analysis of PAMPA [23].…”
Section: Introductionmentioning
confidence: 99%
“…[33b, 42] Recently, Dryfe et al [57] examined the effect of a bipolar ITIES in a supported liquid membrane (SLM)…”
Section: Simple Ion Transfer (It) Reactionsmentioning
confidence: 99%
“…Although some groups [58] around the world had already addressed the behaviour of membranes with two polarisable interfaces, the main trend with SLMs has been the investigation of only a single polarisable interface. In this work, [57] the transfer of analytes across the membrane was followed with a photosensitive probe (rhodamine) via UV-vis absorbance, so as to determine the ion distribution profiles in the SLMs. It also showed that both the membrane and aqueous phases can behave as donor/acceptor phases due to the reversibility of the system.…”
Section: Simple Ion Transfer (It) Reactionsmentioning
confidence: 99%